Expression of Circulating microRNA-141 and mRNA of PTEN (Phosphatase and Tensin Homolog) in Blood Plasma of Ovarian Tumor and Epithelial Ovarian Cancer Patient - AS. Fitriawan; SN Chasanah; FK Pakun; AI Kartika; R. Oktriani; A. Trirahmanto; H. Prajatmo; A. Ghozali; T. Aryandono; SM. Harjana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
Epithelial Ovarian Cancer (EOC) is the most lethal gynecological malignancies among woman. The majority of this disease is diagnosed at the advanced stage due to lack of specific symptoms and effective screening methods. Therefore, an adequate biomarker for early detection is needed and may improve patient survival. microRNA is a small non-coding RNA that regulates gene expression in post-transcriptional level. Several studies have shown the ability to detect microRNA in blood circulation so microRNA may be used as a minimally invasive biomarker for EOC. microRNA-141 (miR-141) plays a major role in EOC by regulating expression of several tumor suppressor gene. Previous study have confirmed that miR-141 regulated PTEN gene directly by interacting with 3’UTR sequence of PTEN mRNA, and upregulation of miR-141 caused downregulation of PTEN expression in vivo. PTEN is important tumor suppressor gene that its inactivation found in various human cancer. PTEN is protein with lipid phosphatase activity that negatively regulate PI3K-AKT signaling pathway, thus playing a important role in various cellular process such as proliferation, growth, cell survival, EMT, cell motility, and angiogenesis. When various studies found that PTEN mRNA and protein expression is significantly downregulated in EOC tissue, little is known about the expression of PTEN mRNA in blood circulation of EOC patient, especially in Yogyakarta population.The aims of this study is to measure and to investigate the correlation of miR-141 and mRNA PTEN expression in plasma of ovarian tumor patient and EOC patient.This study used cross-sectional design. 25 blood plasma of ovarian tumor and 25 blood plasma of EOC were collected. Total RNA was isolated and reverse transcribed to obtain cDNA. The expression of miR-141 and mRNA PTEN were measured by quantitative real-time polymerase chain reaction assay (qPCR). The 2^(-∆∆cq) method was used to calculate relative quantification of miR-141 and mRNA PTEN using miR-16 as reference gene for microRNA and beta-actin mRNA as reference genes for PTEN mRNA. Expression of miR-141 is significantly elevated in blood plasma of epithelial ovarian cancer patient compared to the ovarian tumor (p=0,001, fold change=7,59). Expression of PTEN mRNA significantly downregulated in blood plasma of epithelial ovarian cancer patient compared to the ovarian tumor (p=0,001, fold change=11,63). There was a significant negative correlation between miR-141 expression and mRNA PTEN expression in blood plasma of epithelial ovarian cancer patient (p=0,033; r=-0,428).miR-141 and mRNA PTEN differentially expressed in blood plasma of ovarian tumor and epithelial ovarian cancer patient. There was a negative correlation between miR-141 and mRNA PTEN expression in blood plasma of epithelial ovarian cancer patient. Keywords: Epithelial ovarian cancer, circulating microRNA, miR-141, PTEN mRNA